2017
DOI: 10.1039/c6py01425a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalizing natural polymers with alkoxysilane coupling agents: reacting 3-glycidoxypropyl trimethoxysilane with poly(γ-glutamic acid) and gelatin

Abstract: Hybrid materials, with co-networks of organic and inorganic components, are increasing in popularity due to their tailorable degradation rates and mechanical properties. To increase mechanical stability, particularly in water, covalent bonding must occur between the components. This can be introduced using crosslinking agents such as 3-glycidoxypropyl trimethoxysilane (GPTMS). Attachment of GPTMS to polymers in aqueous conditions is hypothesized to occur by opening of the epoxide ring by nucleophiles on the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…In class II hybrids, the inorganic and the organic components are covalently crosslinked at the molecular level, and thus they cannot be distinguished at microscale. Connell et al and Wang et al 6,10 confirmed that the hybrid reaction occurred between the epoxide ring of the 3-glycidoxypropyl trimethoxysilane (GPTMS) by the primary amine group (\\NH 2 ) of the CS, and they used inorganic/organic weight ratios (I/Os) and molar ratios of CS and GPTMS showed great influence on the inorganic/organic coupling, the mechanical properties, the degradation behavior, and the scaffold morphology. [4][5][6] In addition, both inorganic and organic components have a congruent degradation behavior and hybrids have the potential for tailoring the material properties such as mechanical properties, degradation rate, scaffold morphology, and others.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In class II hybrids, the inorganic and the organic components are covalently crosslinked at the molecular level, and thus they cannot be distinguished at microscale. Connell et al and Wang et al 6,10 confirmed that the hybrid reaction occurred between the epoxide ring of the 3-glycidoxypropyl trimethoxysilane (GPTMS) by the primary amine group (\\NH 2 ) of the CS, and they used inorganic/organic weight ratios (I/Os) and molar ratios of CS and GPTMS showed great influence on the inorganic/organic coupling, the mechanical properties, the degradation behavior, and the scaffold morphology. [4][5][6] In addition, both inorganic and organic components have a congruent degradation behavior and hybrids have the potential for tailoring the material properties such as mechanical properties, degradation rate, scaffold morphology, and others.…”
Section: Introductionmentioning
confidence: 97%
“…[4][5][6] In addition, both inorganic and organic components have a congruent degradation behavior and hybrids have the potential for tailoring the material properties such as mechanical properties, degradation rate, scaffold morphology, and others. 1-3 Some properties of HOIM are distinctly different to that of the parent inorganic and organic elements.…”
Section: Introductionmentioning
confidence: 99%
“…26 Moreover, we noticed that the band of C]O stretching vibration at 1736 cm À1 which corresponds to the free carboxylic acid (COOH) greatly decreased and new symmetric stretching band at 1419 cm À1 which are assigned to the characteristic bands of carboxyl anion (COO-) appeared, as shown in Fig. 2a.…”
Section: 23mentioning
confidence: 87%
“…3, two signals could be clearly distinguished with typical shis of À57 and À67 ppm which corresponding to the T 2 and T 3 . 24 And the peak area of T 3 was larger than T 2 (T 1 ) in all samples. The weak (absence) of T 1 and the dominance of T 3 suggested that condensation reactions between the silanols from GPTMS alkoxides proceed, agreeing with the results of FTIR in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation